2015
DOI: 10.1002/app.42869
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties study of micro‐ and nano‐hydroxyapatite reinforced ultrahigh molecular weight polyethylene composites

Abstract: This is a comparative study between ultrahigh molecular weight polyethylene (UHMWPE) reinforced with micro-and nano-hydroxyapatite (HA) under different filler content. The micro-and nano-HA/UHMWPE composites were prepared by hotpressing method, and then compression strength, ball indentation hardness, creep resistance, friction, and wear properties were investigated. To explore mechanisms of these properties, differential scanning calorimetry, infrared spectrum, wettability, and scanning electron microscopy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…The COF of the composite containing X‐UHMWPE irradiated at 50 kGy almost linearly decreased from 0.2 to 0.15 with increasing the content of X‐UHMWPE from 0 to 25 wt %. However, the COF of the composite containing X‐UHMWPE irradiated at 150 kGy decreased first but increased at a content of 15 wt %, showing great difference but in agreement with the literature . Although the COFs of the two series of specimens differed, the wear rate decreased with the X‐UHMWPE content.…”
Section: Resultssupporting
confidence: 88%
“…The COF of the composite containing X‐UHMWPE irradiated at 50 kGy almost linearly decreased from 0.2 to 0.15 with increasing the content of X‐UHMWPE from 0 to 25 wt %. However, the COF of the composite containing X‐UHMWPE irradiated at 150 kGy decreased first but increased at a content of 15 wt %, showing great difference but in agreement with the literature . Although the COFs of the two series of specimens differed, the wear rate decreased with the X‐UHMWPE content.…”
Section: Resultssupporting
confidence: 88%
“…With small amount of fillers with high aspect ratio the entire polymer is converted into an interfacial polymer with desirable properties . They do exhibit excellent mechanical properties on comparison with those of microcomposites, even with small quantity of nanofillers. They also exhibit increased thermal, chemical, and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the shrinkage cannot be measured or observed in this investigation, the shrinkage of the fibers remains a consequence of small changes in polymer morphology with temperature elevation. Previous work has shown that the UHMWPE fibers used in this experiment undergo an alpha‐relaxation above 80 °C, but degradation may be accelerated at higher temperatures. The statement is further confirmed by remarkably different morphology of the fiber prepared under different temperature.…”
Section: Resultsmentioning
confidence: 94%
“…Initially, the bend deformation of resin matrix was the dominant damage of the laminate, corresponding to the lower slope of load–displacement curves. With the increasing of indenter's displacement, the slope of the curves obviously increased, indicating that the dominant damage transformed to the stretch of UHMWPE fibers and matrix and interfacial debonding between fibers and matrix . Eventually, the load on the laminate decreased.…”
Section: Resultsmentioning
confidence: 99%